Cambridge School : the life, work and influence of James Ward, W.H.R. Rivers, C.S. Myers and Sir Frederic Bartlett - Crampton, Colin (The University of Edinburgh, 1978)
This thesis deals with the biographies, the academic work and the influence of James Ward, W.H.R. Rivers, C.S. Myers and Sir Frederic Bartlett. Along with Galton, Sully, Spearman and Burt these four men were among the principle founding fathers of British psychology. Ward, Rivers and Myers were largely responsible for establishing psychology at Cambridge, where, under Bartlett, the subject later flourished. Part 1 of this thesis argues that these Cambridge pioneers have not yet received the historical attention which befits their cardinal position in British psychology. Part 2 describes Ward's philosophy, systematic psychology and his advocacy of psychophysics. The importance for Ward's thought of Bain, Lotze and Fechner and more generally, of British Associationism and neo Hegelian Idealism, are described. A biography of Ward is presented with special reference to his long struggle to establish psychophysics at Cambridge between 1877 and 1897. Part 3 describes the consolidation of psychology under Rivers and Myers between 1897 and 1922. The life of each man is described illustrating their common background in medicine, anthropology and early experimental psychology. Their work on "Shell Shock" in World War I, their work in experimental and cross cultural psychology, and Myers' massive contribution to industrial psychology, through his N.I.I.P., are outlined. Part 4 looks at the further growth of Cambridge psychology under Sir Frederic Bartlett from 1922 - 1939. His main contributions, it is argued, were; as an experimentalist; as a psychological theorist; as a promoter of applied psychology; as a respected and influential teacher. Special attention is paid to Remembering. Part 5 sums up the work of the Cambridge School. As a detailed history the thesis ends with 1939 but this last section also deals briefly with the influence of the Cambridge School since that date and describes the later work of Bartlett.
Keywords: Cambridge School; Psychology; Ward, James, 1843-1925; Rivers, W. H. R. (William Halse Rivers), 1864-1922; Myers, Charles S. (Charles Samuel), 1873-1946; Bartlett, F. C., Sir (Frederic Charles), 1886-1969